Proceedings of the 33rd Annual ACM Conference Extended Abstracts on Human Factors in Computing Systems 2015
DOI: 10.1145/2702613.2732883
|View full text |Cite
|
Sign up to set email alerts
|

Touchology

Abstract: This paper presents Touchology, interactive plant projects that explore serenity and emotional attachment through meditative touch of plants with interactive audio-visualizations. Gardening is seen to improve mindfulness, memory and cognitive abilities. Those who are unable to benefit from this activity, such as the mentally and physically disabled are less prone to be exposed to the leisure. Due to simple technical setups, the projects presented here can be placed anywhere at the ease of the user. The pilot s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Mindfulness can be defined [181] as acceptance of the moment through non-judgment. In this category, five papers are novel designs [14,133,146,154,168], two are studies of previously developed applications [137,153] and two present studies for understanding how to better design mindfulness in general, outside of therapeutic settings [80,181].…”
Section: Analysis Of Reviewed Work System Functionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mindfulness can be defined [181] as acceptance of the moment through non-judgment. In this category, five papers are novel designs [14,133,146,154,168], two are studies of previously developed applications [137,153] and two present studies for understanding how to better design mindfulness in general, outside of therapeutic settings [80,181].…”
Section: Analysis Of Reviewed Work System Functionsmentioning
confidence: 99%
“…Here, mindfulness appears within a context of issues such as acceptance and distress tolerance, through teaching the person to accept the things they cannot change. Seo et al [146] developed a system aimed at promoting calmness and a feeling of being at ease through touching and interacting with plants. It was tested in children with autism and older adults living in a senior home.…”
Section: Analysis Of Reviewed Work System Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…33 substudies were conducted in a place where the autistic users were not initially familiar with (e.g. research lab [50], gallery [48]). 30 of them didn't mention whether the autistic users were familiarized with the environment (or the people included in the setting) or not.…”
Section: Environment Tools and Materialsmentioning
confidence: 99%
“…Another artwork that was evaluated with both autistic children and seniors in an assisted living facility includes Flora Touch by Seo et al, that used interactive grass and plants as a way to generate light or sound through touch (Seo et al 2015). It was found that seniors were less hesitant to engage than the children, and they stayed with the objects longer, and began discussing their gardening memories with other residents.…”
Section: Introductionmentioning
confidence: 99%